2014
DOI: 10.1103/physrevb.90.144109
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelastic switching of doped zirconia: Modeling and understanding from first principles

Abstract: The properties of materials at high temperatures are often determined by complex thermodynamic mechanisms. One of the most prominent examples is the stabilization of tetragonal and cubic zirconia, which we investigate using density functional theory. The results show that the minimum energy path for the tetragonal-to-cubic phase transformation differs significantly from the paths discussed in the literature so far. This provides insight into the properties of compositions codoped with yttria and titania, an ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 27 publications
(64 reference statements)
3
30
0
Order By: Relevance
“…These are symmetrically distributed around the tiltless cubic perovskite. Similar transition mechanisms have recently been proposed also in several non-perovskite materials [18][19][20][21][22].…”
Section: Introductionsupporting
confidence: 79%
“…These are symmetrically distributed around the tiltless cubic perovskite. Similar transition mechanisms have recently been proposed also in several non-perovskite materials [18][19][20][21][22].…”
Section: Introductionsupporting
confidence: 79%
“…This allows for the emergence of the cubic perovskite structure as a dynamical average at lower temperatures than what would be expected in a picture where the phase transition happens by a displacive mechanism. A similar situation was found for the tetragonal-to-cubic phase transition in ZrO 2 [51].…”
Section: Discussion: Displacive Vs Order-disorder Phase Transitionsupporting
confidence: 51%
“…Their analysis predicted a second-order tetragonal-to-cubic transition of a displacive nature, whereby the average value of the shuffle amplitude gradually decreases to zero upon approaching the transition temperature from below. Carbogno et al 25 also investigated the tetragonal and cubic forms of ZrO 2 with molecular dynamics simulations using PBEsol. They found that thermal excitations induce spontaneous switching between tetragonal shuffle orientations and concluded that the experimental cubic form of ZrO 2 exists as a thermodynamic average of all three tetragonal displacement orientations.…”
Section: Discussionmentioning
confidence: 99%
“…Previously calculated lattice parameters for the cubic phase have ranges between 5.034 -5.151Å 22,23,25,36 . Calculated tetragonal lattice parameters vary between a = 5.029 − 5.161Å and c = 5.100 − 5.383Å 22,23,25,36 . The variation in calculated lattice parameters can likely be attributed to a variety of pseudopotentials being used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation